2014
DOI: 10.1002/cncr.29041
|View full text |Cite|
|
Sign up to set email alerts
|

Cancers associated with BRCA1 and BRCA2 mutations other than breast and ovarian

Abstract: Background Previous studies have reported additional cancers associated with BRCA mutations; however, type, magnitude of risk, and gender differences remain to be clarified. The purpose of this study was to evaluate the incidence of cancers other than breast and ovarian cancer in known mutation carriers. Methods An institutional review board approved study identified 1072 patients who had genetic counseling at our institution and tested positive for a deleterious BRCA mutation. The expected number of cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
299
1
13

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 434 publications
(335 citation statements)
references
References 25 publications
8
299
1
13
Order By: Relevance
“…The results confirm the recognized increased incidence of breast and ovarian cancer in women with a BRCA mutation. Additionally, our results further confirm an association between BRCA mutations and pancreatic cancer.The increased SIRs for breast and ovarian cancer in both BRCA1 and BRCA2 families and for pancreatic cancer in BRCA2 families are consistent with the results from Mersch et al [9], who examined the incidence of non-breast and ovarian cancers in BRCA mutation-positive individuals. The cohort analyzed in the study by Mersch et al [9] represent most of the index cases used to obtain the population of FDRs and SDRs in our study.The increased incidence of prostate cancer in BRCA2 mutation carriers found by Mersch et al [9] was also supported by our findings when analyzing only FDRs in the study population.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results confirm the recognized increased incidence of breast and ovarian cancer in women with a BRCA mutation. Additionally, our results further confirm an association between BRCA mutations and pancreatic cancer.The increased SIRs for breast and ovarian cancer in both BRCA1 and BRCA2 families and for pancreatic cancer in BRCA2 families are consistent with the results from Mersch et al [9], who examined the incidence of non-breast and ovarian cancers in BRCA mutation-positive individuals. The cohort analyzed in the study by Mersch et al [9] represent most of the index cases used to obtain the population of FDRs and SDRs in our study.The increased incidence of prostate cancer in BRCA2 mutation carriers found by Mersch et al [9] was also supported by our findings when analyzing only FDRs in the study population.…”
Section: Discussionsupporting
confidence: 89%
“…One of the larger studies to date, completed by the Breast Cancer Linkage Consortium in 1999 found BRCA2 mutation carriers have an increased risk of prostate and pancreatic cancer and an increased risk of buccal cavity, pharyngeal, stomach, gallbladder, andbile ductcancers and melanoma of theskin [5].Theincreased risk of prostate and pancreatic cancer has been replicated by numerous other studies, and the association between BRCA2 mutations and these cancers is accepted in clinical practice [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 20% of breast cancer patients were BRCA mutations carriers [51,52]. Beyond breast cancer, several other malignancies, including ovarian cancer, pancreatic cancer, melanoma, and prostate cancer, were also correlated to BRCA mutations [53]. On top of BRCA, mutations of other DNA repair genes, such as RAD51, ATM, PALB2, CHEK2, may also increase sensitivity to PARP inhibitors [54].…”
Section: Discussionmentioning
confidence: 99%
“…Bei 90-95 % der Patientinnen besteht eine Mutation im BRCA1-oder BRCA2-Gen [45]. Aber auch für andere Tumoren ist das Risiko erhöht [31].…”
Section: Molekularpathologieunclassified